Kualitas Spermatozoa Epididimis Kambing Kacang dalam Bahan Pengencer Tris Kuning Telur pada Suhu 5°C - Harissatria Harissatria; J. Hendri; Jaswandi Jaswandi; Hendri Hendri; F. Afrianti (State Islamic University of Sultan Syarif Kasim Riau, 2020)
The purpose of this study was to observe the quality of the epididymal spermatozoa of the Kacang goats which were preserved at 5°C. Spermatozoa are taken from epididymal of Kacang goats in Payakumbuh City Slaughterhouse for 10 pairs and collected with a combination of the slicing method and suppression of the epididymal canal. The parameters observed were the percentage of progressive motility, live sperm and abnormalities. The data analyzed by Analysis of Variance in the form of a randomized block design with four treatments and six replications of the retrieval days as a group. The results showed that the percentage of progressive motility of epididymal spermatozoa after preservation of 0, 1, 2 and 3 hours was not significant (P>0.05). Furthermore, the percentage of life has a very significant effect (P<0.01) with the highest average treatment value obtained at the shelf life to 0 hours which is 66.875±19.49%. The percentage of abnormality did not have a significant effect (P>0.05). It can be concluded that the effect of preservation of different cauda epididymal semen at a temperature of 5°C has not been optimal yet in improving the quality of epididymal spermatozoa of Kacang goats.